PENGARUH PENAMBAHAN LIMBAH UDANG PADA PUPUK CAIR DARI FERMENTASI URIN SAPI TERHADAP KUALITAS UNSUR HARA MAKRO - Renaldi Purba; Endro Sutrisno; Sri Sumiyati (Jurnal Teknik Lingkungan, 2013)
The husbandry activity processes will result side products,  known as waste such as feces and urine. The characteristic of these waste are renewable and very potential to be used as liquid fertilizer. On this research, urine from cow is used as raw material for liquid fertilizer because of its nutrient element. One of the techniques to make liquid ferltilizer by fermentation. This research have six variations by adding different amount of  shrimp waste in order to know the best effect of macronutrient element for liquid fertilizer. Variation of the addition are: 0 gr; 15 gr; 30 gr; 45 gr; 60 gr; 75 gr and fermentated for 14 days. The best addition of shrimp waste for good liquid fertilizer is 60 gr addition of shrimp waste, which have nutrient element content of macro C-organic, Nitrogen, Phospor, and Kalium with each percentage 6,75%, 1,62%, 0,63%, and 0,73%.